Por entre as memórias de uma instituição : o arquivo e as práticas administrativas do Atheneu Sergipense (1870-1926) - Santana, Sayonara Rodrigues do Nascimento (2012)
This research has been proposed to analyze the changes and continuity in the organization and conservation of school archive from Atheneu Sergipense and their relationship to the administration practices from 1870 to 1926. Therefore, we use the theoretical assumptions of Antonio Viñao Frago (1995; 2002; 2008), as regards about the concept of school culture, with emphasis on culture, school supplies, and Roger Chartier (1990), particularly the concept of representations. We have searched also some assumptions and concepts of archival theory, mainly Heloisa L. Bellotto (2004), Ana Maria de Camargo and Heloisa L. Bellotto (1996) and Theodore R. Schellemberg (2006). And about of that concerning, we have analyzed the minutes of the Congregation, the mails which were dispatched and reports from Atheneu Sergipense, as well as the legislation educational in this period. Finally, we noted that the history of archive from Atheneu Sergipense has a is conected with the spaces that sheltered the institution over the years, as well as administrative practices, developed by your employees.